CHARACTERS’ ENHANCEMENTS IN THE SERIES ADAPTATION OF LEAGUE OF LEGENDS - Fadhillah, Muhammad Alif; Faiza, Anjania Muhammad; Subari, Afta Ikhlasul; Biela, Bening Salsa; Ibrahim, Yusuf (UIN Raden Mas Said Surakarta, 2024)
Arcane is a TV series adaptation from a game named League of Legends and was categorized as the best TV series in 2021. When many TV series adaptations take novel as its source, this adaptation becomes interesting to analyse because the source text is from a game. This research aims to find out the changes applied to the characters in the series adaptation using Linda Hutcheon’s adaptation theory, in which she mentioned that character is one of aspects often changed when a work is adapted into different form. The Arcane is based on Zaun and Piltover's past, there will be so much to compare from the TV series and the game. Using qualitative method and spradley’s data analysis steps, this research reveal that changes are applied to the characters Vi, Jinx, and Caitlyn. These changes involve appearance, outfit, and ability, which gives more realistic and grounded effect to Arcane’s story. This is due to the different mode of engagement that Hutcheon calls from interacting to showing. With some adjustments made to the characters, the series are able to present engaging story and new audience.